MPO (Myeloperoxidase) Reduces Endothelial Glycocalyx Thickness Dependent on Its Cationic Charge. Issue 8 (August 2018) - Manchanda, Kashish; Kolarova, Hana; Kerkenpaß, Christina; Mollenhauer, Martin; Vitecek, Jan; Rudolph, Volker; Kubala, Lukas; Baldus, Stephan; Adam, Matti; Klinke, Anna
Abstract : Objective—: The leukocyte heme-enzyme MPO (myeloperoxidase) exerts proinflammatory effects on the vascular system primarily linked to its catalytic properties. Recent studies have shown that MPO, depending on its cationic charge, mediates neutrophil recruitment and activation. Here, we further investigated MPO's extracatalytic properties and its effect on endothelial glycocalyx (EG) integrity. Approach and Results—: In vivo staining of murine cremaster muscle vessels with Alcian Blue 8GX provided evidence of an MPO-dependent decrease in anionic charge of the EG. MPO binding to the glycocalyx was further characterized using Chinese hamster ovary cells and its glycosaminoglycan mutants—pgsA-745 (mutant Chinese hamster ovary cells lacking heparan sulfate and chondroitin sulfate glycosaminoglycan) and pgsD-677 (mutant Chinese hamster ovary cells lacking heparan sulfate glycosaminoglycan), which revealed heparan sulfate as the main mediator of MPO binding. Further, EG integrity was assessed in terms of thickness using intravital microscopy of murine cremaster muscle. A significant reduction in EG thickness was observed on infusion of catalytically active MPO, as well as mutant inactive MPO and cationic polymer polylysine. Similar effects were also observed in wild-type mice after a local inflammatory stimulus but not in MPO-knockout mice. The reduction in EG thickness was reversed after removal of vessel-bound MPO, suggesting a possible physical collapse of the EG. Last, experiments with in vivo neutrophil depletion revealed that MPO also induced neutrophil-mediated shedding of the EG core protein, Sdc1 (syndecan-1). Conclusions—: These findings provide evidence that MPO, via ionic interaction with heparan sulfate side chains, can cause neutrophil-dependent Sdc1 shedding and collapse of the EG structure. Abstract : Supplemental Digital Content is available in the text.